1988
DOI: 10.1016/0014-5793(88)81233-x
|View full text |Cite
|
Sign up to set email alerts
|

Excitation‐contraction coupling in skeletal muscle fibers injected with the InsP3blocker, heparin

Abstract: Heparin, an inhibitor of inositol trisphosphate (InsP,)-induced CaZ+ release in smooth muscle and non-muscle cells, was injected into intact frog skeletal muscle fibres. CaZ+ release from the sarcoplasmic reticulum was elicited by the normal action potential mechanism and monitored by both fura-fluorescence and an intrinsic birefringence signal. Both optical signals, and hence Cd+ release, were unaffected by high concentrations of heparin. This result argues against a major physiological role of InsP, as a che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1990
1990
2005
2005

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…However, in connection with skeletal muscle, controversial results have been reported regarding the ability of heparin to inhibit the InsP3 -i n d u c e d r e l e a s e o f C a t o r t o b l o c k E -C c o u p l i n g [35,36]. We have previously shown that lengthening of muscle fibers beyond 3.70 tm of sarcomere length induced an irreversible increase in [Ca2+]i (> pCa6) [1].…”
Section: Discussionmentioning
confidence: 97%
“…However, in connection with skeletal muscle, controversial results have been reported regarding the ability of heparin to inhibit the InsP3 -i n d u c e d r e l e a s e o f C a t o r t o b l o c k E -C c o u p l i n g [35,36]. We have previously shown that lengthening of muscle fibers beyond 3.70 tm of sarcomere length induced an irreversible increase in [Ca2+]i (> pCa6) [1].…”
Section: Discussionmentioning
confidence: 97%
“…This compound was first used to block mitochondrial Ca 2+ transport (Moore, 1971). Later it was shown to inhibit Ca 2+ release from the SR of striated and smooth muscles (Ohnishi, 1979;Miyamoto and Racker, 1982;Antoniu, Kim, Morii, and Ikemoto, 1985;Pampe, Konishi, Baylor, and Somlyo, 1988). It is capable of quenching the efflux of 45Ca from the junctional SR vesicles within milliseconds after addition (Ikemoto, Antoniu, and Meszaros, 1985;Meissner, Darling, and Eveleth, 1986;Sumbilla and Inesi, 1987;Calviello and Chiesi, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…The effect of extracellular heparin on mammalian muscle is controversial: the ryanodine receptor (RyR) is activated by heparin in vitro (Ritov et al, 1985;Bezprozvanny et al, 1993), and the heparin antagonist protamine reversibly blocks the RyR (Koulen and Ehrlich, 2000). Paradoxically, the structurally similar inositol trisphosphate receptor (InsP3R) is inhibited by heparin (Gosh et al, 1988;Kobayashi et al, 1988), whereas in frog muscle heparin cannot activate RyR nor inhibit InsP3R (Pape et al, 1988;Rojas and Jamovich, 1990). Heparin also affects the kinetic properties of the dihydropyridine receptor (DHPR; Knaus et al, 1990;Martinez et al, 1996): intracellular application blocks excitation-contraction coupling in toad (but not in rat) muscle fibers, an effect likely caused by desensitizing the DHPR voltage sensor (Lamb et al, 1994).…”
Section: Hs In Excitation-contraction Couplingmentioning
confidence: 99%